2014
DOI: 10.1073/pnas.1408439111
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic population mapping using mobile phone data

Abstract: During the past few decades, technologies such as remote sensing, geographical information systems, and global positioning systems have transformed the way the distribution of human population is studied and modeled in space and time. However, the mapping of populations remains constrained by the logistics of censuses and surveys. Consequently, spatially detailed changes across scales of days, weeks, or months, or even year to year, are difficult to assess and limit the application of human population maps in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
560
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 752 publications
(568 citation statements)
references
References 60 publications
3
560
0
5
Order By: Relevance
“…Using GPS trajectory data from taxi drivers, Liu et al (2010) [14] revealed taxi drivers' spatial selection of routes and their operation behaviors. Deville (2014) [15] introduced a new approach using mobile phone data to estimate dynamic population densities in near real time.…”
Section: Introductionmentioning
confidence: 99%
“…Using GPS trajectory data from taxi drivers, Liu et al (2010) [14] revealed taxi drivers' spatial selection of routes and their operation behaviors. Deville (2014) [15] introduced a new approach using mobile phone data to estimate dynamic population densities in near real time.…”
Section: Introductionmentioning
confidence: 99%
“…Source: modyfi ed after Murshed (2009) Lately, spatio-temporal population modelling techniques have been introduced. They can distinguish population during day and night or even hourly population distribution using mobile phone footprints (Deville et al, 2014), Call Detail Records (CDRs) and Person Trip Survey (PTS) data from users of mobile devices (Horanont and Shibasaki, 2010;Horanont et al, 2015). This paper demonstrates the use of information about buildings location and their characteristic derived from Topographic Object Database, the nationwide topographic database at the scale 1:10,000, to elaborate gridded population surface for the rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Some national censuses are published at high spatial resolution (100 m) grid format (e.g., Austria [50]), but still remain static, primarily residential, counts. Increasing prevalence of social media and mobile telephony data analysis may provide future opportunities to advance the work presented here further or point towards a potential validation mechanism [51,52].…”
Section: Population L-fp R100 L-fp R250 L-fp R500 Fmz3mentioning
confidence: 95%